Survey of Different Control Strategies for the Regulation of Hemodynamic Variables - D. Sathish, Alamelu Nachiappan (International Journal of Control and Automation, 2020)
In the postoperative period cardiac surgery and critical care units, the automatic control of drug infusion systems is used for regulating the hemodynamic variables of critical care patients to reduce the complications in hospitals. The designing of automatic controllers to the drug infusion system is a challenging task to the biomedical and the control engineers. This paper reviews several automatic closed-loop control strategies for the regulation of hemodynamic variables using single and multiple drugs. This study also highlights the issues, safety, and robustness of the controllers for the control of Mean Arterial Blood Pressure (MABP) and Cardiac Output (CO). The control techniques discussed in this study are Proportional Integral Derivative (PID), Adaptive, Self-tuning, Model Reference Adaptive Control (MRAC), Predictive, Fuzzy-based, and Neural Network controllers.